REPRESENTASI RELIGIOSITAS DALAM CAMPUR KODE DAN ALIH KODE TUTURAN ACARA SINIAR BERBEDA TAPI BERSAMA - Yahya, Mad; Santriani Utari Azim, Nur (STKIP Siliwangi, 2024)
In this article, the author aims to analyze the forms of language variation in the event Berbeda Tapi Bersama (BTB) and its correlation with the speakers’ religious identity. A qualitative method approach was used in this study with data sources derived from three episodes of the BTB podcast. Data was collected using transcription techniques from the verbal utterances of the participants in the program. The study results show variations in speech in the form of code mixing and code switching originating from various languages such as Arabic, Javanese, Hebrew, and Latin. These code-mixing and code-switching forms are linguistic expressions related to the religiosity aspects of the participants. The identification found five categories related to these language variations i.e. vocative utterances, religious rituals, codes or terms originating from the holy book, and the naming of religious groups. Based on the code-mixing and code-switching that is used, Arabic was spoken by Muslim speakers, Latin and Javanese by Christian speakers, and Hebrew by Jewish speakers. The difference in the tendency of code-mixing and code-switching represents the different religious identities of the speakers in the BTB program.